Contagion, Monsoons, and Domestic Turmoil in Indonesia : A Case Study in the Asian Currency Crisis - Saxena, Sweta (IMF Working Papers; Working Paper ;, 2000)
This paper investigates whether Indonesia's recent currency crisis was due to domestic fundamentals, common external shocks ('monsoons'), or contagion from neighboring countries. Markov-switching models attribute speculative pressure on Indonesia's currency to domestic political and financial factors and contagion from speculative pressures in Thailand and Korea. In particular, the results from a time-varying transition probability Markov-switching model (which overcomes some drawbacks of previous methods) show that inclusion of exchange rate pressures from Thailand and Korea in the transition probabilities improves the conditional probabilities of crisis in Indonesia. There is also evidence of contagion in the stock market.